2020
DOI: 10.3390/ijerph17124461
|View full text |Cite
|
Sign up to set email alerts
|

Who or What Influences the Individuals’ Decision-Making Process Regarding Vaccinations?

Abstract: Thanks to vaccines, many people are not exposed to the risks associated with vaccine-preventable diseases (VPDs). This, however, results in growing popularity of antivaccine movements and affects global and local epidemiological situation. Vaccine hesitancy has become a significant problem not only for epidemiologists but also for practitioners. Fortunately, the hesitant group seems to be vulnerable to intervention, and studies indicate that these patients can be persuaded to undergo vaccinations. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 39 publications
(41 reference statements)
3
30
1
Order By: Relevance
“…Professional support must be present in all forms of application of online media and social marketing in the field of immunization as important segment of public health. In this regard, the provision of information by health professionals and the quality of their information are essential for the decision to vaccinate or otherwise [ 77 , 78 ], which is extremely important for communication through social media, which are very common today.…”
Section: Discussionmentioning
confidence: 99%
“…Professional support must be present in all forms of application of online media and social marketing in the field of immunization as important segment of public health. In this regard, the provision of information by health professionals and the quality of their information are essential for the decision to vaccinate or otherwise [ 77 , 78 ], which is extremely important for communication through social media, which are very common today.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers should pay attention to this topic when informing patients and their household contacts about the vaccination. Not all patients will be influenced by receiving first-hand information [34], but earlier studies have shown that giving patients high-quality information about the vaccination raises the vaccination rates [35,36]. The majority of the patients (65.1%) and first household contacts (77.4%) got vaccinated at the recommendation of their GP, while only seven patients and three household contacts were vaccinated at the recommendation of the patients' oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers should pay attention to this topic when informing patients and their household contacts about the vaccination. Not all patients will be influenced by receiving first-hand information [ 34 ], but earlier studies have shown that giving patients high-quality information about the vaccination raises the vaccination rates [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Italy showed that vaccine hesitancy was associated with perceived economic hardship and actual refusal with a lower level of parental education [29]. Greater age, receiving information on vaccinations from a physician and the higher quality of such information as well as better knowledge about vaccines were associated with a more positive attitude towards vaccination in a mixed group of Polish pupils, students, patients, parents and healthcare professionals [30].…”
Section: Discussionmentioning
confidence: 99%